Analisis Efektivitas Web Pembaruan Sistem Inti Administrasi Perpajakan (PSIAP) sebagai Solusi Pembuatan Faktur Pajak Keluaran di PT Petrokimia Gresik - Helvyyana Wulandari; Yulianti Raharjo (Jurnal Riset Akuntansi Politala, 2026)
The era of Digitalization 5.0 has encouraged various institutions to continuously develop technology with the expectation of enhancing efficiency and effectiveness in administrative processes, including in the field of taxation. The Directorate General of Taxes (DJP) introduced Coretax as a digital-based tax administration system to support compliance and improve the convenience of tax services. However, the implementation of Coretax in practice, including at PT Petrokimia Gresik, has encountered several technical obstacles, such as system errors that result in delays in issuing tax invoices. In response to these challenges, PT Petrokimia Gresik initiated the use of the Tax Administration Core System Renewal (PSIAP) web innovation as an alternative to improve the efficiency and reliability of tax invoice issuance. This study aims to analyze the effectiveness of the PSIAP web innovation in addressing the limitations of Coretax, particularly in the issuance of output tax invoices. The research employed a descriptive qualitative method, with data collected through observations and interviews with the tax staff of PT Petrokimia Gresik. The findings reveal that while PSIAP effective in facilitating the creation of non-subsidized tax invoices more quickly and accurately through a batch processing system. PSIAP successfully supports the issuance of non-subsidized tax invoices in a faster, more accurate, and structured manner. Nevertheless, it still faces limitations in accommodating the issuance of subsidized tax invoices, an aspect that remains under continuous improvement.